Monitoring prisoners preparing for release: Who ‘fails’ in open prison conditions? - Goodley, Gary (European journal of criminology, 2024)
Open prisons play a vital role in offender rehabilitation and resettlement but absconds, temporary release failures (TRFs) and re-offences have damaging implications for the legitimacy of these institutions. Identifying and mitigating the risk for such ?failures? is crucial. The present study examined predictors of failure in a sample of 316 adult male prisoners in two open prisons in England and Wales. Almost one-third (n?=?100) of the sample failed in open conditions, the greatest proportion (n?=?83, 26.3%) instigated by the prison to maintain security and good order (security recall). Yet, only seven re-offended in the year following custodial release. Absconds, custodial re-offences, and TRFs were rare events. Regression analysis identified five factors predicting security recall. Current behaviour, rather than static/historical risk factors, more reliably predicted such failures. Behavioural monitoring and systemic policy re-evaluation are proposed as way of mitigating failures in open prisons.